Microfacies and paleodepositional setting interpretation of the latest Oligocene to earliest Miocene Carbonate of Citarate Fm., Bayah High, West Java - Hainim, Iwan (Ikatan Ahli Geologi Indonesia, 2024)
Four hundred and ten samples were collected from carbonate outcrops of Citarate Formation in the Bayah High area, west of Pelabuhan Ratu, West Java. Petrographic analysis reveals 14 carbonate microfacies distributed in the study area, which include: (1) Globigerinid wackestone-packstone, (2) Foraminiferal bioclastic packstone-grainstone, (3) Foraminiferal algal packstone-grainstone, (4) Benthic foraminifera-rich grainstone, (5) Red algal foraminifera packstone, (6) Globigerinid bioclastic packstone, (7) Coralline algal packstone-boundstone, (8) Branching coral packstone-grainstone, (9) Foraminifera coralgal packstone-grainstone, (10) Platy coral foraminiferal algal packstone-grainstone, (11) Intraclast/plagioclase-rich packstone-grainstone, (12) Massive coral boundstone-rudstone, (13) Platy coral bioclastic packstone-grainstone, and (14) Platy coral boundstone grainstone.Micropaleontological analysis of the carbonate microfacies reveals age distribution ranging from P22, N4, to younger than N4 (Blow’s Zonation), and Te4 (Adam’s letter stage), which are equivalent with the latest Oligocene to very Early Miocene Epoch.Detailed stratigraphic observation from outcrops and micropaleontological analysis show a north-south carbonate trend. This trend happened to superimpose the structural lineaments of Bayah High. It is interpreted that a shallow depositional environment developed in the western part and became deeper towards the east.This paper is part of a study of Oligo-Miocene carbonates and their relationship to tectonic events in West Java. By knowing the evolution of Oligo-Miocene carbonate rocks and their relationship with the tectonic development of West Java, it is possible to interpret the presence of these carbonate rocks below the surface for hydrocarbon exploration purposes.